Pengembangan Budaya Organisasi dalam Lembaga Pendidikan Islam di SMA Cerdas Murni - Marsyela Marsyela; Marsyeli Marsyeli; Tasya Widyana; Nabila Zulfa; Dita Oktaviani; Rizky Akmalia (Journal on Education, 2023)
The context of this research is the biggest challenge for schools or madrasas in carrying out mandates related to the development of culture in Islamic educational institutions which is a benchmark for the success of implementing education in cultural development at Smart Pure High School, one of which is to shape the character or personality of students through inheritance of values. culture value. Culture in schools will experience development and progress, if the culture in an organization and institution is organized and can run well. This cultural development is carried out to meet the complexity of society's demands and respond to the changing times. In developing culture, we must apply the stages of the concept of cultural development which are very relevant to be applied in Islamic educational institutions because they can be used as a focus of reference, especially in achieving the desired goals. As for one of the efforts made by the Pure Intelligent High School in developing the culture towards superior madrasas is to create a full day system at Pure Intelligent High School because the goal is so that Pure Intelligent High School students do not do bad things because of their time lapse, a full day system was created, because In a full day system, all students are only involved in school activities and have no time to do bad things outside of school. This type of research is a qualitative descriptive research based on field research (field research). The results of the study show that the culture developed by Smart Pure High School includes: 1. Full day every Monday to Thursday, Saturday filled with mandatory Scouting activities, 2. There are extracurricular activities for Tahfidz Qur'an, Drumband, Karate, Scouts, 3. Every morning there is Koran reading activities before learning.